Clinical Application of a Modular Genomics Technique in Systemic Lupus Erythematosus: Progress towards Precision Medicine. (30th August 2016) - Zollars, Eric; Courtney, Sean M.; Wolf, Bethany J.; Allaire, Norm; Ranger, Ann; Hardiman, Gary; Petri, Michelle
Abstract : Monitoring disease activity in a complex, heterogeneous disease such as lupus is difficult. Both over- and undertreatment lead to damage. Current standard of care serologies are unreliable. Better measures of disease activity are necessary as we move into the era of precision medicine. We show here the use of a data-driven, modular approach to genomic biomarker development within lupus—specifically lupus nephritis.